Using Water Hyacinth Fiber ( Eichhornia Crassipes) as Heat Absorbers Media In Wall - Muhammad Rahmatullah Amin; Sefri Wahyu Fernando Gultom; Fitrisia Krisa Bella; Putri Lynna A. Luthan (Universitas Negeri Medan, 2019)
Water hyacinth is aquatic weed plant that has medium fiber content with length about 1.75 – 2.12 mm and diameter about 11.15 – 11.65 μm in its stem. Water hyacinth contains 90% of water by weight reduction from 10 Kg when wet to 1 Kg when dry. In dry conditions, water hyacinth contains crude protein 13.03%, crude fiber 20.6%, fat 1.1%, ash 23.8% and the rest is vortex that contains polysaccharides and minerals. Research was done to obtain the design of heat absorbing product that modified with additional of water hyacinth. The method that was uesd begin with drying water hyacinth to obtain good fiber. water hyacinth fibers then mixed with cement and sand which are made as composites in order to reduce the heat of room. The result of the research is make a product that can overcome thermal comfort problems in deep room temperature condition. Water hyacinth was chosen because it is easy to obtain, cheap and can reduce environmental pollution (biodegradability) so that the composite can overcome environment ptoblem and its used doesn’t endanger health. Based on the test result by providing a heat source of 40 Watt bulb lamp to the media for 15 minutes, it was found that the final temperature of the media 1 without additional of water hyacinth fiber was 32.5oC, final temperature of media 2 with additional of 100 gr water hyacinth was 32.2oC, and the final temperature of media 3 with additional 150 gr water hyacinth was 31.7oC. it shows heat temperature that is released and cannot be absorbed by composite in media 3 is only 0.50C, in meida 2 is only 10C while in composite in media 1 without additional of water hyacinth fiber that release heat about 1.3oC. it shows that the product is suitable to use because composite with additional of water hyacinth can absorb heat and release less heat compared to composite without additional water hyacinth fiber so that the room become cooler.